Quantitative Oculomotor and Vestibular Profile in Spinocerebellar Ataxia Type 6 – Systematic Review and Meta-Analysis - Tarnutzer, AA; Garces, P; Antoniades, CA (Springer, 2024)
Whereas several studies have reported on quantitative oculomotor and vestibular measurements in spinocerebellar ataxia type 6 (SCA6), selecting the most suitable paradigms remains challenging. We aimed to address this knowledge gap through a systematic literature review and providing disease-specific recommendations for a tailored set of eye-movement recordings in SCA6. A literature search (MEDLINE, Embase) was performed focusing on studies reporting on quantitative oculomotor and/or vestibular measurements in SCA6-patients. Oculomotor and vestibular parameters were extracted and correlations with various epidemiologic and clinical parameters were sought. Twenty-two studies were included reporting on 154 patients. Abnormalities observed included reduced pursuit gain (58/69), frequent square-wave jerks (23/40), spontaneous downbeat nystagmus (DBN, 34/55) and triggered nystagmus including positional nystagmus (25/34) and vertical (“perverted”) head-shaking nystagmus (21/34), gaze-evoked nystagmus (48/70) and angular vestibulo-ocular reflex (aVOR)-suppression (21/25), and high-frequency aVOR-deficits (26/33). For horizontal visually-guided saccades (VGS), changes in metrics (36/66) were frequently observed, whereas saccade velocity was usually preserved (39/44) and saccade latency within normal limits. Reduced high-frequency aVOR gains, VGS-latency and metrics correlated with disease severity. Longitudinal data indicated deterioration of individual video-head-impulse testing gains over time. A broad range of oculomotor and vestibular domains are affected in SCA6. Impairments in pursuit, saccade metrics, gaze-holding (gaze-evoked nystagmus, DBN) and high-frequency aVOR were most frequently identified and as such, should be prioritized as disease markers. Quantitative oculomotor testing in SCA6 may facilitate an early diagnosis and prove valuable in monitoring disease progression.